Tetrahedral DNA nanostructures synergize with MnO2 to enhance antitumor immunity via promoting STING activation and M1 polarization - Siping Liang; Jiaying Li; Zhengyu Zou; Miao Mao; Siqi Ming; Fan Lin; Ziyan Zhang; Can Cao; Jinyu Zhou; Yuanqing Zhang; Jiaping Li; Minhao Wu (Elsevier, 2022)
Stimulator of interferon genes (STING) is a cytosolic DNA sensor which is regarded as a potential target for antitumor immunotherapy. However, clinical trials of STING agonists display limited anti-tumor effects and dose-dependent side-effects like inflammatory damage and cell toxicity. Here, we showed that tetrahedral DNA nanostructures (TDNs) actively enter macrophages to promote STING activation and M1 polarization in a size-dependent manner, and synergized with Mn2+ to enhance the expressions of IFN-β and iNOS, as well as the co-stimulatory molecules for antigen presentation. Moreover, to reduce the cytotoxicity of Mn2+, we constructed a TDN-MnO2 complex and found that it displayed a much higher efficacy than TDN plus Mn2+ to initiate macrophage activation and anti-tumor response both in vitro and in vivo. Together, our studies explored a novel immune activation effect of TDN in cancer therapy and its synergistic therapeutic outcomes with MnO2. These findings provide new therapeutic opportunities for cancer therapy.